2012
DOI: 10.1137/110831234
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis of Interface Temporal Discretization in Grid Overlapping Methods

Abstract: We investigate the stability of a temporal discretization of interface terms in grid overlapping methods. A matrix stability analysis is performed on a model problem of the one-dimensional diffusion equation on overlapping grids. The scheme stability is first analyzed theoretically, and a proof of the unconditional stability of the first-order interface extrapolation scheme with the firstand second-order time integration for any overlap size is presented. For the higher-order schemes, we obtain explicit estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Search and locate procedures are carried out to express the location of a point on the interface of one subdomain in terms of the local coordinates of a corresponding element in the other subdomain. Temporal coupling at interfaces is achieved using up to a third-order explicit interface extrapolation scheme (IEXT3), using interpolated values from previous time steps [44,56].…”
Section: Methodsmentioning
confidence: 99%
“…Search and locate procedures are carried out to express the location of a point on the interface of one subdomain in terms of the local coordinates of a corresponding element in the other subdomain. Temporal coupling at interfaces is achieved using up to a third-order explicit interface extrapolation scheme (IEXT3), using interpolated values from previous time steps [44,56].…”
Section: Methodsmentioning
confidence: 99%
“…(The nonlinear term is already accurately treated by extrapolation and is stable provided one adheres to standard CFL stability limits.) Typically three to five subiterations (κ iter ) are needed per timestep to ensure stability [24] for mthorder extrapolation of the interface boundary data, when m > 1. Using this approach, Merrill et al [21] demonstrated exponential convergence in space and up to third-order accuracy in time for Schwarz-SEM flow applications.…”
Section: Sem-schwarz For Navier-stokesmentioning
confidence: 99%
“…However, the convergence rate is not great for some FSI couplings, which is why a lot of effort goes into convergence acceleration [10]. An alternative are optimized Schwarz methods [13,15,29] and the CHAMP scheme (Conjugate Heat transfer Advanced Multidomain Partitioned) which uses a generalized Robin (mixed) condition at the interface to accelerate the iteration [24], but overlapping domains. Furthermore, for incompressible fluids it is known that the ratio of densities of the materials plays an important role [1,9].…”
Section: Introductionmentioning
confidence: 99%